Nutritional values of wild edible freshwater macrophytes - Zakaria, Muta Harah; Ramaiya, Shiamala Devi; Bidin, Nordiah; Syed, Nurul Nur Farahin (PeerJ, 2023)
Freshwater macrophytes have been determined for the proximate composition and mineral content of three freshwater macrophytes species, Eichhornia crassipes, Limnocharis flava, and Neptunia oleracea. Young shoots of E. crassipes, L. flava, and N. oleracea were collected from shallow channels of Puchong, Ladang 10, Universiti Putra Malaysia and Kg. Alur Selibong, Langgar, Kedah, Peninsular Malaysia. Eight replicates of E. crassipes and L. flava and four replicates of N. oleracea were used for subsequent analyses. In the proximate analysis, N. oleracea possessed the highest percentage of crude protein (29.61) and energy content (4,269.65 cal g−1), whereas L. flava had the highest percentage of crude fat (5.75) and ash (18.31). The proximate composition trend for each species was different; specifically, all of the species possessed more carbohydrates and fewer crude lipids. All of the species demonstrated a similar mineral trend, with high nitrogen and potassium and lower copper contents. Nitrogen and potassium levels ranged from 12,380–40,380 mg kg−1 and from 11,212-33,276 mg kg−1, respectively, and copper levels ranged from 16–27 mg kg−1. The results showed that all three plant species, i.e., E. crassipes, N. oleracea, and L. flava are plant-based sources of macro- and micronutrient beneficial supplements for human consumption.